Alternative countrysides Anthropological approaches to rural Western Europe today - MacClancy, Jeremy (Manchester University Press, 2015)
A fresh anthropological look at a central but neglected topic: the profound changes in rural life throughout Western Europe today. As locals leave for jobs in cities they are replaced by neo-hippies, lifestyle-seekers, eco-activists, and labour migrants from beyond the EU.With detailed ethnographic examples, contributors analyse new modes of living rurally and emerging forms of social organisation. As incomers' dreams come up against residents' realities, they detail the clashes and the cooperations between old and new residents. They make us rethink the rural/urban divide, investigate regionalists' politicisation of rural life and heritage, and reveal how locals use EU monies to prop up or challenge existing hierarchies. They expose the consequences of and reactions to grand EU-restructuring policies, which at times threaten to turn the countryside into a manicured playground for escapee urbanites.This book will appeal to anyone seriously interested in the realities of rural life.